Removal of dyes from industrial effluents using combination of advanced oxidation processes (AOPs) and biological treatment - Che Zulzikrami Azner Abidin (School of Environmental Engineering, University Malaysia Perlis, 2014)
On the whole, the COD removal was similar to TOC removal for each treatment. It is obvious that high decolourization from the start of biological was contributed from ozonation pre-treatment. In addition, the results indicate that 59.6 and 69.4% COD removal from ozonation and ozonation-biological, respectively for MO.